2008
DOI: 10.1111/j.1447-0594.2008.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stroke‐induced damage to swallow‐related areas in the brain on swallowing mechanics of elderly patients

Abstract: Damage to swallow-related areas may reduce their sensitivity to incoming signals from the oral cavity thereby impairing preparations to generate motor command signals and compromising their ability to send sufficient voluntary descending command signals to activate the swallowing central pattern generator located in the medulla. This deficiency becomes more evident with successive swallows and manifests as impaired swallowing mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Patients with stroke have a reported frequency of dysphagia in recent studies, ranging from approximately 50–80% [7]. Mechanics of swallowing dysfunction included reduced hyoid excursion, reduced tongue base retraction, and reduced pharyngeal shortening [810]. Many studies have found that dysphagia is association with subtype and severity of stroke [11].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with stroke have a reported frequency of dysphagia in recent studies, ranging from approximately 50–80% [7]. Mechanics of swallowing dysfunction included reduced hyoid excursion, reduced tongue base retraction, and reduced pharyngeal shortening [810]. Many studies have found that dysphagia is association with subtype and severity of stroke [11].…”
Section: Discussionmentioning
confidence: 99%
“…Current literature of the functional changes in stroke related dysphagia emphasizes delays in timing [6–8], aspiration risk associated with timing [911], and related sensorineural deficits [1214] with mechanistic deficits receiving less attention. Reports suggest differences in hyoid and laryngeal displacement but are mixed (Table 1) [11, 1518].…”
Section: Introductionmentioning
confidence: 99%
“…1994; Abraham and Yun 2002; Warabi et al. 2008; Terré and Mearin 2012). Pharyngeal swallow delay frequently results in aspiration of thin liquids and potentially pneumonia (Morton et al.…”
Section: Introductionmentioning
confidence: 99%
“…2007; Warabi et al. 2008). Stroke patients with dysphagia have been shown to demonstrate significant sensory deficits in the laryngopharynx that likely contribute to the development of aspiration (Aviv et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation